Hijacking homeostasis: the brain-body neural circuitry in tumor pathogenesis and emerging therapeutic frontiers - Yong-Fei Wang; Zi-Kai Dong; Wei-Lin Jin (Molecular Cancer)
Abstract Cancer research is undergoing a paradigm shift from solely studying tumor cells to investigating systemic effects of cancer in the tumor macroevironment, with an emphasis on the interactions between host organs and tumors. The theory of homeostasis is an important basis for explaining biological functions from the perspective of the organism. Organic homeostasis relies on brain-body crosstalk through interception, immunoception, nociception and other supervisory processes, guaranteeing normal physiological function. Recent studies reveal that malignant tumors can hijack and exploit the brain and its central-peripheral neuronal networks to disrupt the body's homeostasis. Tumors likely disrupt normal brain-body crosstalk by establishing bidirectional brain-tumor connections. On the contrary, organism utilize these mechanisms to hinder tumorigenesis and progression. Standing at the perspective of brain-body crosstalk also promotes the conceptional evolution of cancer initiation and development, and more importantly, provides additional insight for cancer treatment. In this review, we summarize current knowledge about brain-body crosstalk under tumor-bearing contexts and propose some novel anti-cancer strategies. Graphical Abstract Brain-body crosstalk participates in the battle between tumors and the organism: The homeostasis of the organism is collectively maintained by interoception, nociception, neuroception, endocriception, metaboception and immunoception. However, in tumor states, tumors hijack the brain-body crosstalk system to exploit these homeostatic mechanisms, thereby constructing a macroenvironment conducive to their survival and progression. While tumors hijack the brain-body crosstalk to reestablish homeostasis, the host organism simultaneously counteracts the tumor through brain-body crosstalk, safeguarding its intrinsic homeostasis from disruption. The brain-body crosstalk between tumors and multiple organs mediated by the HPA axis-driven humoral regulation and the sympathetic and parasympathetic nerves plays a significant role in the battle between tumors and the organism. TME, tumor microenvironment; HPA, hypothalamic-pituitary-adrenal; SAS, sympatho-adrenal system. This figure was created using BioRender ( https://biorender.com/ ).